Efektivitas Pemasaran Produk Tabungan Syariah BATARA iB BTN Pada Masa Pandemi - Yusuf, Junaedi; Isnandar, Fajri Ryan (At-Tamwil: Journal of Islamic Economics and Finance, 2025)
This research aims to analyze the marketing strategy of the Bank Tabungan Negara (BTN) Batara iB product during the COVID-19 pandemic, focusing on a case study at BTN Syariah Branch Office (KC) Bekasi. The research employs a field research method with a descriptive qualitative approach. Data were collected through direct observation and interviews with key stakeholders. The identified marketing strategies include direct selling methods such as cross selling, open table, door-to-door, and personal selling. The study also applies the marketing mix framework, which includes four main elements: product, price, place, and promotion. The findings indicate that conventional marketing activities were limited due to pandemic restrictions, prompting BTN Syariah KC Bekasi to shift its marketing strategies to digital platforms. The promotion of the Batara iB product was carried out through social media channels such as the official website, Instagram, Facebook, and YouTube. This digital transformation is seen as a strategic adaptation to social distancing measures and the increasing digitalization of banking services. The online marketing approach proved effective in maintaining product visibility and reaching a broader customer base. This study is expected to serve as a reference for developing sharia banking marketing strategies during crises and in post-crisis periods.